Sphingosine 1-Phosphate Signaling as a Target in Hepatic Fibrosis Therapy - González-Fernández, Bárbara; Sánchez, Diana I.; González-Gallego, Javier; Tuñón, María J. (Frontiers in Pharmacology, 2017)
Liver fibrosis is a result of wound healing response to chronic injury defined by an excess production of extracellular matrix leading to organ dysfunction. The key cells involved in fibrogenesis are resident hepatic stellate cells (HSCs) which are termed myofibroblasts after activation, acquiring contractile, proliferative, migratory and secretory capability. Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid with well-established effects on angiogenesis, carcinogenesis and immunity. Accumulating evidence demonstrates that this metabolite is involved in the profibrotic inflammatory process through the regulation of pleiotropic cell responses, such as vascular permeability, leukocyte infiltration, cell survival, migration, proliferation and HSCs differentiation to miofibroblasts. S1P is synthesized by sphingosine kinases (SphKs) and many of its actions are mediated by specific cell surface receptors (S1PRs), although important direct intracellular targets of S1P have been identified. Modulation of SphKs/S1P/S1PRs signaling is known to result in beneficial effects on various in vivo and in vitro models of liver fibrosis. Thus, a better knowledge of the molecular mechanisms involved in the modulation of the S1P pathway could help to improve liver fibrosis therapy. In this review, we highlight the effects of the S1P axis on the fibrogenic process, and the involvement of a range of inhibitors or approaches targeting enzymes related to S1P in the abrogation of pathological fibrogenesis. All in all, targeting this pathway offers therapeutic potential in the treatment of hepatic fibrosis.